2020
DOI: 10.1016/j.ijrobp.2020.07.987
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Radiation Dose to the Amygdala on Emotional and Social Cognition and Depressive Symptoms

Abstract: Purpose/Objective(s): One of the most difficult steps of the radiotherapy is to determine the clinical target volume (CTV) based on the microscopic extension (ME). The aim of this study was to evaluate the ME in gliomas using consecutive macropathology. Another objective was to identify the predictive factors which could determine the ME. Materials/Methods: The study included glioma patients with tumor locating in the non-functional area and the gross maximal resection (between 2-3cm away from the tumor border… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…51 Although amygdala atrophy has been correlated with impaired function and cognition in Alzheimer disease, Huntington disease, and temporal lobe epilepsy, for example, amygdala volume as a biomarker for post-RT dysfunction is under investigation. Hardy et al 52 reported in abstract form on 28 patients with primary brain tumors that higher mean RT dose to either the right or left amygdala was positively correlated with increase in subjective depression symptoms at 3 months post-RT on the Patient Health Questionnaire 2. Another study, however, found only hippocampal dosimetric correlations with posttreatment Hopkins Verbal Learning Test scores, with no association between amygdala dose and cognitive dysfunction.…”
Section: Amygdala Volumementioning
confidence: 99%
“…51 Although amygdala atrophy has been correlated with impaired function and cognition in Alzheimer disease, Huntington disease, and temporal lobe epilepsy, for example, amygdala volume as a biomarker for post-RT dysfunction is under investigation. Hardy et al 52 reported in abstract form on 28 patients with primary brain tumors that higher mean RT dose to either the right or left amygdala was positively correlated with increase in subjective depression symptoms at 3 months post-RT on the Patient Health Questionnaire 2. Another study, however, found only hippocampal dosimetric correlations with posttreatment Hopkins Verbal Learning Test scores, with no association between amygdala dose and cognitive dysfunction.…”
Section: Amygdala Volumementioning
confidence: 99%